CFD and statistical analysis of flow mass ratios on temperature and pressure drops of double pipe heat exchanger - EVRAN, SAVAŞ; KURT, MUSTAFA (My University, 2023)
In this numerical and statistical study, the effect of mass flow rates for shell and fluid temperature for tube on temperature and pressure drops was analyzed in double pipe heat exchanger under counterflow. Numerical calculations were performed using computational fluid dynamics (CFD) in ANSYS Fluent. Calculations were carried out according to the L8 orthogonal array with two control factors in accordance with Taguchi method. Although the different mass flow rates of the fluid passing through the shell were chosen as the first control factor, different fluid temperatures of the fluid passing through the tube were selected for the second control factor. Signal-to-noise ratio analysis was used to decide the impacts and optimum levels of the mass flow rates and fluid temperatures on temperature and pressure drop. The significance levels and contribution percentages of each variable on the temperature and pressure change occurring in the heat exchanger were calculated using analysis of variance. The accuracy of the analyses was compared numerically and statistically by comparing the obtained optimum CFD results with the estimated Taguchi results. This study can be used as a guiding research in the project and cost calculations of heat exchangers to be produced experimentally
Keywords: Makina Mühendisliği; Mühendislik ve Teknoloji; Mechanical Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Fizik Bilimleri; Computational Mechanics; Automotive Engineering; Physical Sciences; Taguchi method; ANOVA; pressure; temperature; CFD; heat exchanger